Value Creation Through Negotiations in Collaborative Networks (Revista Interdisciplinar de Marketing, 2017)
Consumer research has examined the process of value creation in collaborative contexts through studies of brand communities and similar collectives. Nevertheless, extant research falls short of explaining value creation that happens in collaborative networks, where a variety of participants, including consumers, entrepreneurs, and companies interact. It is not clear, for example, whether consensus is necessary to determine what value is and how it is created in these highly heterogeneous networks. Drawing from data collected through a blended ethnography and netnography of the collaborative network of geocaching, this study examines value creation in collaborative networks. Findings suggest that value creation initiates with value propositions negotiated by participants in use, across contexts, through time, and within relationships. These findings challenge arguments that co-created value is achieved by social consensus among beneficiaries, rather indicating that ongoing negotiation among participants may replace social consensus as the ultimate determinant of value. This study provides insight on the formation of cultures of co-creation, and explains how different moments in the process of collaborative value creation can be leveraged by marketers, entrepreneurs, and consumers who participate in value-creating networks.